Estudio de factibilidad para la implementación de ganadería intensiva en el rancho ecológico San Andrés - Alulema Albán, Marlon Andrés (2021)
With this study, I proposed to verify the feasibility of the implementation of an intensive livestock system for the period of 5 years in the San Andrés Ecological Ranch of the Pastocalle parish, Latacunga canton, Cotopaxi Province. Due to the study I have determined the unsatisfied demand for milk in the domestic market. It is necessary to determine the viability of the increase in the company's production. The land used for the implementation of the project is 3 Hectáreas (Ha); 2.93. Ha will be earmarked for the cultivation of pasture and the rest will be earmarked for infrastructure. The amount of productive cattle that will be used in this project is 37 heads of dairy cattle: Jersey breed and their cross breeds, which will generate an average daily production of 14 liters per cow. In order to do this project, $70,080 is needed, which will be financed by a bank for a term of 5 years. The results obtained through the calculations made, a NPV of $53,091.76 and an IRR of 33% are estimated. Therefore the project represents an important investment opportunity. In conclusion, with the projected revenues, positive cash flows have been obtained for the expected time, which allows to have a clear vision for the future with respect to the economic development of the project and therefore the project is considered feasible to implement in the company.